24(S)-Hydroxycholesterol as a Modulator of Neuronal Signaling and Survival. (April 2016) - Sun, Min-Yu; Linsenbardt, Andrew J.; Emnett, Christine M.; Eisenman, Lawrence N.; Izumi, Yukitoshi; Zorumski, Charles F.; Mennerick, Steve
The major cholesterol metabolite in brain, 24(S)-hydroxycholesterol (24S-HC), serves as a vehicle for cholesterol removal. Its effects on neuronal function, however, have only recently begun to be investigated. Here, we review that nascent work. Our own studies have demonstrated that 24S-HC has potent positive modulatory effects on N -methyl-d -aspartate (NMDA) receptor (NMDAR) function. This could have implications not only for brain plasticity but also for pathological NMDAR overuse. Other work has demonstrated effects of 24S-HC on neuronal survival and as a possible biomarker of neurodegenerative disease. Depending on circumstances, both upregulation/mimicry of 24S-HC signaling and down-regulation/antagonism may have therapeutic potential. We are interested in the possibility that synthetic analogues of 24S-HC with positive effects at NMDARs may hold neurotherapeutic promise, given the role of NMDA receptor hypofunction in certain neuropsychiatric disorders.